2013
DOI: 10.1016/j.juro.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Protein Signature for the Detection of Bladder Cancer in Voided Urine Samples

Abstract: Purpose Accurate urine assays for bladder cancer detection would benefit patients and health care systems. Through extensive genomic and proteomic profiling of urine components we previously identified a panel of 8 biomarkers that can facilitate the detection of bladder cancer in voided urine samples. In this study we confirmed this diagnostic molecular signature in a diverse multicenter cohort. Materials and Methods We performed a case-control, phase II study in which we analyzed voided urine from 102 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 30 publications
(33 reference statements)
5
61
0
2
Order By: Relevance
“…Previous studies have reported a positive correlation between MMP-10 and PAI-1 [41-43]. Similar, we report an increase of both MMP-10 and PAI-1 in voided urine samples from subjects with bladder cancer [21,22]. Interesting, Wilkins et al reported that the addition of PAI-1 blocks collagen degradation as well as the conversion of MMP-10 to its catalytically active form.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have reported a positive correlation between MMP-10 and PAI-1 [41-43]. Similar, we report an increase of both MMP-10 and PAI-1 in voided urine samples from subjects with bladder cancer [21,22]. Interesting, Wilkins et al reported that the addition of PAI-1 blocks collagen degradation as well as the conversion of MMP-10 to its catalytically active form.…”
Section: Discussionsupporting
confidence: 89%
“…We have previously reported a significant increase in the expression of MMP-10 transcripts in shed urothelia from patients bearing bladder tumors relative to healthy controls [20], and we subsequently confirmed that increased soluble MMP-10 protein levels were indicative of bladder cancer in two large, independent studies [21,22]. In this study, we evaluated MMP-10 expression through immunohistochemical staining of a commercial bladder cancer TMA (70 benign samples and 188 cancer samples).…”
Section: Resultsmentioning
confidence: 53%
“…The potential of such an approach is demonstrated in numerous studies published by Rosser and collaborators. [69][70][71][72][73][74][75][76][77][78] A 10-biomarker panel consisting of i nterleukin-8, matrix metalloproteinase (MMP)9, MMP10, α-1-antitrypsin, vascular endothelial growth factor A, angiogenin, carbonic anhydrase 9, apolipoprotein E, syndecan-1 and plasminogen activator inhibitor 1 was developed based on the consolidation of data derived from various 'omics' approaches including transcriptomics 72,75 and proteomics 55 followed by individual validation in immunebased assays, which measured single proteins. 70,73,74,[76][77][78] The diagnostic capabilities of this panel were assessed in an external multicentre study of 320 individuals, of which 183 had primary urothelial carcinomas, 96 had benign urological disorders, including voiding symptoms, urolithiasis, UTIs and/or haematuria, and 41 healthy individuals.…”
Section: Multi-marker Panelsmentioning
confidence: 99%
“…Patients under surveillance for recurrent bladder cancer are more likely to present with low-stage bladder cancer. Our program of refining our candidate panels of biomarkers in a series of validation cohorts may have avoided this issue (7, 8). Continued bladder tumor recurrence after an initial diagnosis may be explained by the field-cancerization theory (25).…”
Section: Discussionmentioning
confidence: 99%
“…We have subsequently reported the validation of the 10-biomarker diagnostic panel in a large cohort of patients ( n = 308), which included controls with diverse urologic conditions (e.g., urolithiasis, moderate-to-severe voiding symptoms, urinary tract infection, and hematuria; ref. 8) and through analysis of samples obtained from multiple sites in the United States and in Europe ( n = 320; Chen and colleagues, submitted for publication) in an external laboratory. In the current study, we set out to evaluate the performance of the 10 urinary biomarkers in our primary bladder cancer detection panel to detect recurrent bladder cancer in a multicenter cohort composed of patients with a history of bladder cancer undergoing routine surveillance.…”
Section: Introductionmentioning
confidence: 99%